Impact of chronic morphine on delta opioid receptor-expressing neurons in the mouse hippocampus. (28th January 2016) - Erbs, E.; Faget, L.; Ceredig, R.A.; Matifas, A.; Vonesch, J.-L.; Kieffer, B.L.; Massotte, D.
Highlights: Chronic morphine decreases the density of delta receptor-expressing neurons. Chronic morphine equally affects all delta opioid receptor-expressing populations. Chronic morphine increases cell surface expression of delta opioid receptors. Mu opioid receptors are required to observe chronic morphine effects. Most changes induced by chronic morphine persist after four weeks of abstinence. Abstract: Delta opioid (DOP) receptors participate to the control of chronic pain and emotional responses. Recent data also identified their implication in spatial memory and drug-context associations pointing to a critical role of hippocampal delta receptors. To better appreciate the impact of repeated drug exposure on their modulatory activity, we used fluorescent knock-in mice that express a functional delta receptor fused at its carboxy-terminus with the green fluorescent protein in place of the native receptor. We then tested the impact of chronic morphine treatment on the density and distribution of delta receptor-expressing cells in the hippocampus. A decrease in delta receptor-positive cell density was observed in the CA1, CA3 and dentate gyrus without alteration of the distribution across the different GABAergic populations that mainly express delta receptors. This effect partly persisted after four weeks of morphine abstinence. In addition, we observed increased DOP receptor expression at the cell surface compared to saline-treated animals. In the hippocampus, chronic morphine administration thus induces DOP receptor cellular redistribution and durably decreases delta receptor-expressing cell density. Such modifications are likely to alter hippocampal physiology, and to contribute to long-term cognitive deficits.